Nature-based experiences in tree houses: guests' online reviews. Issue 3 (12th June 2019) - Brochado, Ana
Abstract : Purpose: This study aims to examine nature-based tourists' experiences in tree houses using user-generated content in Web reviews. The research objectives were to identify the main dimensions of tree house experiences and test whether these dimensions vary according to different traveller-type market segments. Design/methodology/approach: A sample of 722 Web reviews was analysed using mixed content analysis methods. Leximancer software provided computer-assisted qualitative data analysis that identified the main themes, after which further qualitative analysis identified the key narratives associated with experiences. Findings: The results reveal that tourists are extremely satisfied with their stays in tree houses. The main themes that encompass the dominant narratives are tree house, Costa Rica, staff, morning, walk, wildlife, rainforest, opportunity to learn, trip, experience and recommendation. The narratives vary according to type of traveller. Originality/value: The valuable insights gained emphasise the advantages of using user-generated content in tourism studies. The results also offer a better understanding of the key dimensions of this type of nature-based tourism, including a graphic representation of the main themes and concepts in guests' narratives. In addition, the findings emphasise that nature-based tourists are not a homogeneous group and that they can be segmented according to type of traveller.